Maternal anaemia prevention and control in China: A policy review - Xiaoxi Liu; Xiaona Huang; Yuning Yang; Anuradha Narayan; Lidan Du‐Skabrin; Xue Ding; Yongchao Chen; Jun Zhao; Suying Chang; Fang Wang (Wiley, 2024)
Abstract Maternal anaemia is a major public health problem. Developing maternal anaemia prevention and control policies is an important prerequisite for carrying out evidence‐based interventions. This article reviews maternal anaemia prevention and control policies in China, identifies gaps, and provides references for other countries. We examined policies concerning maternal nutrition and other related literature in China, identified through key databases and government websites, and conducted a narrative review of the relevant documentations guided by the Smith Policy‐Implementing‐Process framework. A total of 65 articles and documents were identified for analysis. We found that Chinese government has committed to reducing maternal anaemia at the policy level, with established objectives and a clear time frame. However, most of policies were not accompanied by operational guidelines, standardized interventions, and vigorous monitoring and evaluation mechanisms, and 85% of the policies don't have quantifiable objectives on anaemia. Maternal anaemia prevention and control services offered in clinical settings were primarily nutrition education and anaemia screening. Population‐based interventions such as iron fortification have yet to be scaled up. Furthermore, medical insurance schemes in some regions do not cover anaemia prevention and treatment, and in other regions that offer coverage, the reimbursement rate is low. The number and capacity of health professionals is also limited. Policy changes should focus on the integration of evidence‐based interventions into routine antenatal care services and public health service packages, standardization of dosages and provision of iron supplementation, streamline of reimbursement for outpatient expenses, and capacity building of health professionals.